Ebelik Öğrencilerinin Ebelik Eğitiminin Akreditasyonu Konusundaki Görüş ve Algıları. - EKŞİOĞLU, Aysun; HADIMLI, Aytül; DEMİR, Emine; AKAN, Ayşenur; CEBER TUFAN, Esin (Journal of Nursology, 2023)
Objective: This research was conducted to examine the perceptions and opinions of midwifery students about the accreditation of midwifery education. Methods: The cross-sectional study was carried out with a total of 418 students studying in the midwifery department of a university between March and April 2022. The data were collected by online data collection method, using a questionnaire and "Accreditation Perception Scale," The data were analyzed using the Statistical Package for Social Sciences version 22 package program. Results: About 68.7% of the students know what accreditation means, 54.5% think that it will benefit students and graduates. The general average score of the Accreditation Perception Scale of the students is 4.09 ± 0.98. The general average of the Quality Assurance sub-dimension is 4.08 ± 0.99, and the general average of the Quality Evaluation sub-dimension is 4.10 ± 0.97. The average score of the students is high according to the item level acceptance classification. Accreditation perception scale scores were found to be significantly higher in those who participated in the scientific event, knew the purpose of accreditation, internal/external stakeholders, wanted to take part in accreditation studies, knew the quality ambassadors and the mission/vision of the department (P < .001). Conclusion: In this study, it was determined that midwifery students found accreditation beneficial and had a supportive attitude in this regard. The active participation of students in accreditation studies and the organization of awareness education on this subject can be effective in the recognition and adoption of accreditation.